2008
DOI: 10.1021/ja076663z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Synthetic Strategy:  Total Synthesis of (±)-Welwitindolinone A Isonitrile

Abstract: An efficient and highly stereoselective total synthesis of the natural product (±)-welwitindolinone A isonitrile (1) is described. The bicyclo[4.2.0]octane core of 1 was established by a regio- and diastereoselective [2+2] ketene cycloaddition. The C12 quaternary center and vicinal stereogenic chlorine were installed in a single operation with excellent stereocontrol via a chloronium ion mediated semipinacol rearrangement. Described strategies for construction of the spiro-oxinole include a SmI2−LiCl mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(71 citation statements)
references
References 53 publications
1
69
0
1
Order By: Relevance
“…[26] The reaction was first explored in the model system 25. These studies demonstrated that SmCl 2 was the reagent of choice for the desired transformation, and that the reaction proceeds by a pathway in which the alkene is coupled to the isocyanate ("alkene first") rather than the more traditional "carbonyl first" mechanism.…”
Section: Samarium(ii) Chloridementioning
confidence: 99%
See 1 more Smart Citation
“…[26] The reaction was first explored in the model system 25. These studies demonstrated that SmCl 2 was the reagent of choice for the desired transformation, and that the reaction proceeds by a pathway in which the alkene is coupled to the isocyanate ("alkene first") rather than the more traditional "carbonyl first" mechanism.…”
Section: Samarium(ii) Chloridementioning
confidence: 99%
“…SmCl 2 -mediated synthesis of oxindoles by the reductive coupling of isocyanates in an approach to welwitindolinone A isonitrile by Wood and co-workers. [26] Scheme 10. A) Reduction of a-heteroatom-substituted carbonyl groups using SmI 2 .…”
Section: Samarium(ii) Chloridementioning
confidence: 99%
“…[97] Unfortunately, the desired product 118a was only obtained as the minor product (up to 16 % with modified conditions) together with the wrong diastereoisomer 118b and small amounts of the dehalogenated product 118c. This strategy was abandoned because the stereoselectivity for this process could not be improved.…”
Section: Oxindoles Through Enolate Arylationsmentioning
confidence: 99%
“…Angewandte Aufsätze D. J. Procter und M. Szostak telter intramolekularer Kupplungen von Isocyanaten auf dem Weg zu einem Isonitril von Welwitindolinon A, einem hochfunktionalisierten Oxindolalkaloid (Schema 9). [26] Die Reaktion wurde zunächst anhand des Modellsystems 25 erforscht. Diese Untersuchungen belegten, dass SmCl 2 das Reagens der Wahl für die gewünschte Reaktion war und dass die Reaktion über einen Mechanismus verläuft, in dem das Alken an das Isocyanat gekuppelt wird ("Alken-zuerst"-Mechanismus) anstelle des traditionelleren "Carbonyl-zuerst"-Mechanismus.…”
Section: Samarium(ii)-chloridunclassified